Asymmetric responses of functional microbes in methane and nitrous oxide emissions to plant invasion: A meta-analysis. (March 2023) - Yao, Yanzhong; Song, Youtao; Su, Pinjie; Wang, Jing; Miao, Congke; Luo, Yifu; Sun, Qiqi; Wang, Jiale; Zhang, Guohui; Bu, Naishun; Li, Zhaolei
Abstract: Plant invasion increases methane (CH4 ) and nitrous oxide (N2 O) emissions, however, the changes of soil functional microbes governing CH4 and N2 O emissions are poorly understood. We conducted a meta-analysis based on 112 published papers to explore soil functional microbes driving CH4 and N2 O emissions under plant invasion. The result showed that CH4 and N2 O emission rates were increased by 94.6% and 27.3% under plant invasion, respectively, and the increments of CH4 and N2 O emission were ascended with time since invasion. The copies of soil functional microbes in the production of CH4 ( mcrA ) and N2 O ( nirS and nirK ) were increased by 105.7%, 24.4%, and 55.1% under plant invasion, respectively, whereas the copies of soil functional microbes in the consumption of CH4 ( pmoA ) and N2 O ( nosZ ) were decreased by 50.4% and 24.5%, respectively. Plant invasion influenced soil functional microbes via increasing above-ground biomass, soil organic carbon, total nitrogen, and microbial biomass carbon. This study highlighted the vital roles of soil functional microbes in CH4 and N2 O emission rates under plant invasion. This study also revealed that the increased CH4 and N2 O emission rates under plant invasion were time-dependent, which challenged the constant estimation of ecosystem warming potential under plant invasion in the long term. Highlights: Responses of CH4 and N2 O differed among categories (e.g. ecosystem types) under plant invasion. Higher CH4 rates were ascribed to asymmetric changes of mcrA and pmoA under plant invasion. Plant invasion increased nirS and nirK, but decreased nosZ, resulting in more N2 O emission. Responses of CH4 and N2 O emissions generally increased with longer invaded time.